Markedly elevated procalcitonin due to anaphylactic shock, a case report - Mohammad Altermanini (16810755) (2022)
Procalcitonin (PCT) is a well-known biomarker that is directly connected to bacterial infection especially when it reaches significantly high levels. It is extremely rare to be witnessed in non-bacterial infections such as viral or parasitic. It may be elevated in other conditions such as trauma and autoimmune diseases. We present a rare case of a young gentleman, who had an extremely high PCT level that appeared to be a result of anaphylaxis due to worm infestation. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2022.e10595